2003
DOI: 10.1111/j.1572-0241.2003.07300.x
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Migraine and Celiac Disease: Results From a Preliminary Case-Control and Therapeutic Study

Abstract: Our results suggest that a significant proportion of patients with migraine may have CD, and that a gluten free diet may lead to a improvement in the migraine in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
4
5

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(70 citation statements)
references
References 18 publications
3
55
4
5
Order By: Relevance
“…All were on a gluten-free diet. Recently, Gabrielli et al 26 demonstrated that a significant proportion of patients with migraine had subclinical CD and that their symptoms improved with a glutenfree diet. This is not the case in epileptic disorders or learning disabilities and ADHD.…”
Section: Discussionmentioning
confidence: 99%
“…All were on a gluten-free diet. Recently, Gabrielli et al 26 demonstrated that a significant proportion of patients with migraine had subclinical CD and that their symptoms improved with a glutenfree diet. This is not the case in epileptic disorders or learning disabilities and ADHD.…”
Section: Discussionmentioning
confidence: 99%
“…The rest 2 groups almost showed neck to neck response rates. In a total of 32 patients who were followed up after a fortnight, 13 patients (41%) have shown > 50% improvement to treatment as depicted in Figure 3 ( 7,12,25,43) As shown in Figure 4, with increase in days of follow-up, response rates to treatment as well as number of patients both showed an increasing trend. But this change, of increase response to treatment is only noted with Group B and C. Among the 3 groups, Group C tops the list in terms of response rates after a period of 1 month.…”
Section: Discussion and Conclusion:-mentioning
confidence: 94%
“…Given the protean clinical manifestations of CD and the expanding list of associated conditions, 24 the strategy of testing for CD for one associated symptom or condition may approach that of screening the general population, since nearly 100% of respondents may respond affirmatively to at least one item. For example, in the case finding study by Catassi, et al, 64% of all participants were eligible for CD testing, and this questionnaire did not include additional items that may be justifiably included in a CD symptom checklist, such as peripheral neuropathy, 25 migraines, 26 gastroesophageal reflux, 27 low bone density 28 and low levels of High-density lipoprotein. 29 A recent study set at a health fair in Caspar, Wyoming sheds light on the fine line between case finding and screening the general population.…”
Section: Identifying the Appropriate Patient To Test For Celiac Diseasementioning
confidence: 99%